Students' Critical Thinking Ability in Solving the Application of the Derivative of Algebraic Function Problems - Marzuki Marzuki; Saiman Saiman; Wahyudin Wahyudin (Didaktik Matematika, 2022)
Critical thinking (CT) is convergent thinking that can be explored when students learn mathematics. Yet, CT based on the level of mathematical ability has not been widely explored. The participants involved 30 Year 11 students in Bandung, Indonesia. The research instruments were a written CT ability test and a semi-structured interview guide. Interviews were conducted in-depth to capture very high mathematical abilities until saturated data were obtained. Data saturation occurred during the interview with the 10th participant, where new categories and sub-categories were no longer found. Data was analyzed following an intrinsic case study design based on the post-positivist paradigm through NVivo 12 plus. This study found that students' CT ability level was very high, their thinking abilities varied, and they able to provide solutions to anyone in solving similar problems. This finding will have implications for the variety of students' critical thinking patterns in learning mathematics on the application of the derivatives of algebraic function in high school.